2020
DOI: 10.1142/s2047684120500232
|View full text |Cite
|
Sign up to set email alerts
|

Refining anticipation of degraded bone microstructures during osteoporosis based on statistical homogenized reconstruction method via quality of connection function

Abstract: Nowadays, osteoporosis disease that is related to aging has become a proliferating problem in worldwide society. It is therefore crucial to understand its evolution and predict this phenomenon precisely for different types of bone and volume fractions with adequate mathematical model. The application of statistical reconstruction method would be a helpful tool to predict osteoporosis for the simplified bone microstructures. To model osteoporosis evolution over time, in a first step, we propose to degrade the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Future works include evaluating the capability of QCF to adequately reconstruct 3D microstructures accounting for the heterogeneous distribution. This work was started in Famouri et al (2021), who showed that the microstructures chosen by QCF in the reconstruction process of 3D trabecular bone were more accurate compared to the one chosen by TPCF.…”
Section: Discussionmentioning
confidence: 99%
“…Future works include evaluating the capability of QCF to adequately reconstruct 3D microstructures accounting for the heterogeneous distribution. This work was started in Famouri et al (2021), who showed that the microstructures chosen by QCF in the reconstruction process of 3D trabecular bone were more accurate compared to the one chosen by TPCF.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, some models have tried to bridge the different scales of bone remodeling (see, e.g., [15][16][17][18]). However, the limited knowledge of bone mechanobiological functioning remains a gap difficult to bridge to validate these models on human patients, particularly when accounting for patient dependency [19][20][21]. It is possible, at the macroscopic scale, to integrate more complex mechanical behavior in order to try accessing the local microstructure distribution that influences the bone density variation, either with or without an implant [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Around macroscopic bone stimulus described generally in Hart [15], Giorgio et al [16] applied to specific microstructured media [17], many researches include the range of adaptative response [18][19][20][21], more physiological approaches [22], optimal response [23][24][25], including viscous and diffusive phenomena [26,27], and cellular automata (CA) [28]. Lately, Famouri et al [29] and Bagherian et al [30] developed a statistical function called quality of connection to more accurately predict the microstructure evolution of bone during osteoporosis based on its volume fraction. But the difficulty lies in the fact that the use of classical continuum mechanics fails when trying to model the local bone mechanobiological effects, particularly at a cellular level, since the continuity of the material is not realistic anymore [31][32][33].…”
Section: Introductionmentioning
confidence: 99%